Influence of vertical loads on lateral behaviour of monopiles in sand. (31st August 2018) - Mu, Linlong; Kang, Xingyu; Feng, Kai; Huang, Maosong; Cao, Jie
Abstract: The monopiles are always subjected to both vertical loads and lateral loads. However, the designs for the piles under the vertical loads and the lateral loads are carried out separately in practice because the interaction between those two loads is still unclear. A series of model tests are carried out to investigate the influence of the vertical loads on the lateral responses of the monopile in sandy soil. The results show that the presence of the vertical load improves the lateral behaviour of the monopile. The influence of the vertical load on p–y curve around the monopile is also investigated to look for a useful suggestion for the design of monopile. In order to calculate the lateral responses of the monopile based on traditional design method, several equations are proposed to evaluate the degree of improvements.